Clinical and Radiographic Outcomes of Immature Teeth Treated with Different Treatment Protocols of Regenerative Endodontic Procedures: A Retrospective Cohort Study - Radovan Žižka (Journal of Clinical Medicine, 2021)
Regenerative endodontic procedure (REP) is a progressive treatment modality for immature permanent teeth with necrotic pulp. The ambiguousness about the predictability of REP outcome in relation to complete disinfection of the root canal system and the occurrence of discoloration still exists. The aim of this retrospective study was to analyze two treatment protocols on clinical success rate, radiographic root development and the occurrence of discoloration. Eighteen patients were treated by a single operator by either treatment protocol according to the American Association of Endodontists (AAEP, n = 9) or a modified protocol (MP, n = 9) with the use of 5% sodium hypochlorite and sandblasting. Patients were followed up after 3, 6, 9, 12, 18 and 24 months and clinical success, radiographic root development and the occurrence of discoloration were assessed. The clinical success of MP was significantly higher in two years follow-up (p = 0.015), but the change in radiographic root area was higher for AAEP (p = 0.017) and the occurrence of discoloration was higher in AAEP (p = 0.029). The use of 5% sodium hypochlorite for a longer period of time leads to a higher success rate. The sandblasting of the access cavity reduces the occurrence of discoloration.